Renal gluconeogenesis: an underestimated role of the kidney in systemic glucose metabolism. Issue 8 (28th November 2020) - Legouis, David; Faivre, Anna; Cippà, Pietro E; de Seigneux, Sophie
ABSTRACT: Glucose levels are tightly regulated at all times. Gluconeogenesis is the metabolic pathway dedicated to glucose synthesis from non-hexose precursors. Gluconeogenesis is critical for glucose homoeostasis, particularly during fasting or stress conditions. The renal contribution to systemic gluconeogenesis is increasingly recognized. During the post-absorptive phase, the kidney accounts for ∼40% of endogenous gluconeogenesis, occurring mainly in the kidney proximal tubule. The main substrate for renal gluconeogenesis is lactate and the process is regulated by insulin and cellular glucose levels, but also by acidosis and stress hormones. The kidney thus plays an important role in the maintenance of glucose and lactate homoeostasis during stress conditions. The impact of acute and chronic kidney disease and proximal tubular injury on gluconeogenesis is not well studied. Recent evidence shows that in both experimental and clinical acute kidney injury, impaired renal gluconeogenesis could significantly participate in systemic metabolic disturbance and thus alter the prognosis. This review summarizes the biochemistry of gluconeogenesis, the current knowledge of kidney gluconeogenesis, its modifications in kidney disease and the clinical relevance of this fundamental biological process in human biology.